2020
DOI: 10.1021/acs.estlett.0c00483
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardant Concentrations Are Lower in College Spaces Meeting the New Furniture Flammability Standard TB117-2013

Abstract: California's updated furniture flammability standard, TB117-2013, can be met without the use of chemical flame retardants (FRs). FRs have been associated with neurological damage, reproductive toxicity, thyroid disease, and cancer. We collected dust from classrooms and other nonresidential spaces on four U.S. college campuses that met one of California's two older FR-reliant standards (TB117, TB133) or the newer TB117-2013. We hypothesized that spaces with TB117-2013-compliant furniture would have lower levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Previous studies have reported that contamination levels of brominated flame retardants (BFRs) in indoor dust from campuses in New England, U.S.A., correlated with legislative changes in furniture flammability standards. 38,39 Specific laws in the USA may have influenced the flame-retardant constituents utilized in the interior furnishings of educational institutions, in turn affecting the BCA concentration in dust.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that contamination levels of brominated flame retardants (BFRs) in indoor dust from campuses in New England, U.S.A., correlated with legislative changes in furniture flammability standards. 38,39 Specific laws in the USA may have influenced the flame-retardant constituents utilized in the interior furnishings of educational institutions, in turn affecting the BCA concentration in dust.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The rooms from which dust containing BCAs were collected included auditoriums, lecture halls, and lounge areas which were carpeted (except for US-5) and generally densely fitted with upholstered furnishings, ranging from 18 furnishings in US-5 to 462 in US-4. Previous studies have reported that contamination levels of brominated flame retardants (BFRs) in indoor dust from campuses in New England, U.S.A., correlated with legislative changes in furniture flammability standards. , Specific laws in the USA may have influenced the flame-retardant constituents utilized in the interior furnishings of educational institutions, in turn affecting the BCA concentration in dust.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in the lowering of indoor air/dust concentrations of flame retardants. 35 Another example of a standard inhibiting the phase out of PFAS is the U.S. Department of Defense (DOD) military specification (referred to as "Mil-Spec") that required the firefighting foams used for extinguishing Class-B fuel fires to contain fluorine or have positive spreading coefficients necessary for film-formation. 16 The Mil-Spec standard was also extended to civilian airports by the US Federal Aeronautics Agency.…”
Section: What Is the Role Of Technical Performance Standards?mentioning
confidence: 99%
“…Studies of other semi-volatile pollutants, such as plasticizers and brominated flame retardants (BFRs), in indoor dust have shown that specific items or furnishings may act as point sources of contamination to significantly affect overall concentrations (Christia et al, 2019;Harrad et al, 2016). The age of particular goods and materials might also influence the distribution of contaminants with regard to historical usage patterns and the potential for enhanced release of contaminants from worn or degrading materials (Rodgers et al, 2020;McGrath et al, 2018). Previous research has also identified seasonal variation in the distribution of CPs in dust and air within indoor environments relating to temperature dependant partitioning (Yuan et al, 2021;Gao et al, 2018), while room ventilation and cleaning habits of the occupants might have the potential to affect dust loading within rooms (Harrad et al, 2008).…”
Section: Introductionmentioning
confidence: 99%